2014
DOI: 10.1136/bmjopen-2014-005834
|View full text |Cite
|
Sign up to set email alerts
|

Improving the uptake of systematic reviews: a systematic review of intervention effectiveness and relevance

Abstract: ObjectiveLittle is known about the barriers, facilitators and interventions that impact on systematic review uptake. The objective of this study was to identify how uptake of systematic reviews can be improved.Selection criteriaStudies were included if they addressed interventions enhancing the uptake of systematic reviews. Reports in any language were included. All decisionmakers were eligible. Studies could be randomised trials, cluster-randomised trials, controlled-clinical trials and before-and-after studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 40 publications
4
50
0
Order By: Relevance
“…These outcomes highlight four points which are consistent with the authors’ previous experience in a wide range of health service projects, earlier SHARE work [4, 7] and the findings of others [8, 9, 12, 15, 76, 89, 90] and reinforce the need for Project Support Services within a local health service.Decisions to proceed with a project to implement change are often made without consideration of research evidence and local data and are not well-defined in terms of the intervention, practitioner group, patient population, indications, etc.Clinicians are frequently asked to undertake projects in their area of clinical expertise but they lack knowledge and skills in project management, implementation and evaluation.Clinicians are usually required to conduct a project in addition to their normal duties but without additional time or resources.Health service staff are well aware of their limitations and those of their colleagues in undertaking projects and they welcome advice and support. …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These outcomes highlight four points which are consistent with the authors’ previous experience in a wide range of health service projects, earlier SHARE work [4, 7] and the findings of others [8, 9, 12, 15, 76, 89, 90] and reinforce the need for Project Support Services within a local health service.Decisions to proceed with a project to implement change are often made without consideration of research evidence and local data and are not well-defined in terms of the intervention, practitioner group, patient population, indications, etc.Clinicians are frequently asked to undertake projects in their area of clinical expertise but they lack knowledge and skills in project management, implementation and evaluation.Clinicians are usually required to conduct a project in addition to their normal duties but without additional time or resources.Health service staff are well aware of their limitations and those of their colleagues in undertaking projects and they welcome advice and support. …”
Section: Resultssupporting
confidence: 90%
“…The findings of the local needs analysis are consistent with the current literature on EBDM using research and/or data [8–12, 15, 52, 62, 65, 91, 92], disinvestment and resource allocation [56–59, 61, 64, 70, 76, 93–95], and information needs of health service decision-makers [39, 40, 43, 45, 53, 89]. More recently, systematic reviews have identified interventions that have been demonstrated to enhance uptake of research evidence and these are also included in the matrix [8, 67, 96–99]. Two systematic reviews of interventions to improve use of data for health service decisions [100] and clinical decisions [101] were unable to find evidence of effective strategies.…”
Section: Resultssupporting
confidence: 84%
“…At the health systems level, lack of relevance of the questions the reviews are addressing, lack of contextualization of findings, unwieldy size of the report, poor presentation format, poor technical infrastructure, poor communication channels, untimeliness of the availability of evidence, lack of access and time to seek and acquire systematic reviews, and lack of skills to appraise and apply the evidence have been identified as barriers to using findings from systematic reviews by decision makers. On the other hand, collaboration between researchers and policy makers, skills development, strengthening networks, and building organizational cultures receptive to embedding evidence in practice have shown to be promising strategies for facilitating evidence uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Baatiema et al (2017) argue that the uptake and adoption of EBGs are often delayed or fail because of a range of barriers across organisational healthcare professional domains, patient care and policies (guidelines). There is some evidence about the barriers, facilitators and interventions that impact on the uptake of evidence from systematic reviews (Wallace, Byrne, & Clarke, 2014). Little is known about what constitutes high quality in guidelines themselves and how this may impact on the uptake of guidelines, although development of guidelines with high quality is one of the fundamental influential factors.…”
Section: Introductionmentioning
confidence: 99%